IMPLEMENTASI MODEL PENDIDIKAN INKLUSIF BERBASIS NILAI-NILAI KRISTIANI - Monalisa Katiok; Phebe Agnes Pakiding; Silpa Zetty; Nelsa Natasha Tombang; Maria (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study aims to explore and analyze the implementation of a Christian values-based inclusive education model in schools. Inclusive education is an approach designed to ensure that all students, including those with special needs, can fully participate in the learning process. In this context, Christian values such as love, justice, equality, and service provide a strong moral and ethical foundation to support inclusive education. This research employs a literature review method to examine related literature on the implementation of inclusive education and the integration of Christian values in education. The findings of the study indicate that a Christian values-based inclusive education model can create a more welcoming, just, and supportive learning environment for all students. The value of love helps to foster a classroom atmosphere of attentiveness and empathy, while the values of justice and equality ensure that all students have equal access to educational opportunities. The value of service teaches the importance of helping and serving others, enriching students' learning experiences. The inclusive classroom model and the collaborative model are two effective approaches for integrating Christian values into inclusive education. The inclusive classroom model emphasizes adapting the curriculum and teaching methods to meet the individual needs of students, whereas the collaborative model involves cooperation between general education teachers and special education teachers to support student needs. The study concludes that Christian values-based inclusive education not only enhances students' academic outcomes but also builds strong character and morals, making them fair, loving individuals ready to serve society.